RUSSIA AND THE SOUTHERN CAUCASUS: REALITY AND ECONOMIC COOPERATION STRATEGIES - ULTANBAEV, Raphael (CENTRAL ASIA AND THE CAUCASUS, 2005)
The Southern Caucasus is one of the most important geopolitical and geoeconomic CIS zones in Russia’s sphere of vitally important interests. One of the main reasons for this is Russia’s close historical, geographical, economic, political, and strategic ties with this region’s countries—Azerbaijan, Armenia, and Georgia. However, the instability in this potentially conflict-intensive region is having a strong impact on the situation in the Northern Caucasus and on the security of the Russian Federation as a whole. The South Caucasian vector is the “hottest” area of Russian foreign policy. It is characterized by dynamic, complicated, and urgent problems, which have geostrategic dimensions. The geo-economic significance of the South ern Caucasus for Russia is defined by many factors. The region has large promising hydrocarbons (in the neighboring Caspian zone) and deposits of polymetallic ores (manganese, cop per and molybdenum concentrates, and so on). Its strategic value as a transit territory is also growing, through which gas and oil pipelines linking Europe and Asia are beginning to be built. The South Caucasian states are also interest ed in close cooperation with Russia. They are tied to their northern neighbor by a common history, cultural and human relations. What is more, these countries are very economically dependent on the Russian Federation. They depend on Russian de liveries of energy resources, metals, lumber, and products of the machine-building and chemical industries, as well as foodstuffs for ensuring their normal functioning, on the one hand. While on the other, Russia is an attractive and receptive sales market for the traditional products of the agro-industrial sector of these countries: tea, tobacco, vegetables, citrus fruit, cotton, wines, as well as industrial commodities and raw materials. What is more, the tension which arose on the labor market due to the lingering conflicts, economic crisis, unemployment, and social instability in these countries has largely been defused by labor migration to the Rus sian Federation. In the past ten years, labor migra tion alone has resulted in the departure of an aver age of 20-25% of the titular nation from the South Caucasian republics. 1 According to the available assessments, the amount of foreign currency legally exported from Russia by the South Caucasian diaspo ras amounts to approximately 5-7 billion dollars a year. It is these transfers that fill the family budgets of much of the South Caucasian population and pre vent a drop in the standard of living below the mark conducive to political destabilization. 2 But despite the favorable prerequisites, in the post-Soviet period, relations between Russia and these states have developed laboriously and contra dictorily, which was due to the ambiguous and in consistent policy of the leaders of these newly in dependent states, as well as to the severe socioeco nomic situation in the region, the unresolved eth nopolitical conflicts, and the opposition of some Western states to rapprochement among the former Soviet republics. The difficult economic situation of the latter compelled them to look for solutions to the econom ic crisis in the “far abroad.” The situation was ag gravated by the Russian Federation’s economic weakness, due to which it could not render the nec essary economic assistance to its South Caucasian partners or become a driving force propelling them out of their quagmire. The faux-pas made by the Russian leadership in its relations with these gov ernments also played a negative role.